Investing in the territory: conditions, criticalities, resources, opportunities - De Albertis, Claudio (TECHNE - Journal of Technology for Architecture and Environment, 2011)
In order for the building sector in Italy to overcome the crisis, general conditions concerning the performance of the Italian economic system must occur and the planned public works projects and announced housing plans must be implemented. The new building cycle will bring with it a different market than the traditional one, hence the need to identify some strategic areas that refer to the current models of supply and demand, in particular the demand for housing which continues to grow and that relative to the transformation of the existing heritage. In the coming years, the challenge for the building sector will be to embark on a process of highly significant innovation, guided by the dynamics of globalization, technological evolution as well as energy and environmental issues.